(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2025)
The culture is the main scene of the incarnation of political and social aspirations, noting that it has been paid in colonias, and it compares to the colonial era in Algeria that travels to France with a church in the middle of the terrain, so that the domain can be found. Education or academic. From these academic institutions, to the projects that serve France and other ambitions, to participate in the Africa revue, this year, which is founded by the creation of the Algerian Historical Societies, to the highest level of academic institutions, orientalistes, and the algerian group participated in the magazine published with permission from 1856 to 1962. Share the sujets abordés from the African Revue in the Algerian desert in different domains, which is the history of the country, the usernames, the mystical sunnite, or the angles, and part of the suction problem: Comment and if the African review is that you like it? What are the first fonds? How do you vote in the Sahara desert in Africa? What’s the matter with the African review in the Algerian desert? To respond to the device you want to delete the domain in the same location as the Sahara Algerian network.